Investigating the hidden ecosystems vibrant underneath hydrothermal vents and deepest oceanic trenches - Vaishnav, Venu Anand Das; Dewangan, Hemlata; Verma, Dr. Monica (International Journal of Aquatic Research and Environmental Studies, 2025)
The distinctive ecosystems and biodiversity linked to Mid-Ocean Ridge (MOR) hydrothermal venting networks starkly differ from adjacent Deepest Oceanic Trenches (DOT); however, both face escalating threats from modern activities, such as mining at enormous sulphide occurrences. Global warming can affect the DOT by raising bottom conditions, depleting oxygen levels, and altering DOT circulation patterns. Notwithstanding the possibility for significant impacts, the processes that allow these structures and their natural environments to endure, operate, and react to maritime, crustal, and anthropogenic stresses are inadequately comprehended. This is mainly attributable to technical obstacles and challenges in obtaining, watching, and tracking the DOT. During the 2000s, a DOT observatory was established to elucidate the interaction among sub-surface flows and oceanic and crustal environments and their impact on biological activities. DOT observatories yield extensive, interdisciplinary time-series information, including repeated surveys and samples at temporal precision ranging from seconds to years, utilizing a blend of cabled, portable, centrally operated, and autonomous measurement equipment. These observatories advocate for stewardship by establishing effective environmental surveillance, which includes characterizing natural and ecological baseline conditions, distinguishing changes due to natural variability from those resulting from human activities, and evaluating degradation, resiliency, and recuperation following disturbances. This underscores the potential of observatories as essential instruments for Ecological Impact Analysis (EIA) on climatic changes and other human activities, particularly ocean mines. This report presents an overview of scientific accomplishments facilitated by the three observatories over the past decade, along with suggestions to enhance future research through international cooperation and coherence. The suggested suggestions encompass: i) the establishment of universal scientific inquiries and the identification of Essentials Ocean Variables (EOVs) pertinent to MORs, ii) directives for the efficient utilization of observatory to inform policies affecting society, iii) methods for the growth of observatories facilities aimed at standardizing detectors, data types, and capacity, and iv) future technological requirements and unified sampling methodologies to address the most pressing contemporary questions.
Keywords: Hydrothermal Vents, Deep Sea, Oceanic Trenches, Ecosystems